EVALUATING REAL ESTATE MARKET IN JAKARTA - Kenly Muliana Pamadi (Fakultas Teknik, Universitas Riau Kepulauan, 2021)
This report aims to evaluate the potential of developing or investing in direct real estate sector in Jakarta. In doing so, firstly, it presents some of the macroeconomic indicators of Indonesia and Jakarta which serve as the foundations for deeper property market analysis. Secondly, it examines the real estate market in Jakarta – the supply and demand, occupancy, price or rent, and future market outlook. The asset class discussed in this report is limited to high-rise residential, CBD and non-CBD office, as well as retail. Thirdly, it describes the institutional or political framework on foreign property development or investment in Indonesia which is increasingly opened to international players but still constrained to certain limitations. This report subsequently analyses the strength, weakness, opportunity, and threat (SWOT) of real estate development or investment in Jakarta. Other crucial topics such as the national capital relocation from Jakarta to East Kalimantan and the issue of recent coronavirus pandemic (COVID-19) and its effect to global recession are also considered. Finally, this report is concluded by presenting the key insights on the subject, including an increasingly popular notion in Transit Oriented Development (TOD) in Jakarta.